A NEW RESOURCE LEVELING MODEL FOR THE CONSTRUCTION PROJECT MANAGEMENT OF BUILDING STRUCTURES: THE GENETIC ALGORITHM - Yesugey, S.Cengiz; Karakaya, Abdulkadir (European Scientific Journal, ESJ, 2014)
In this article, the use of the genetic algorithm method was examined with regards to the optimization of resource leveling during planning studies performed within the scope of the construction project management for buildings. The aim was to develop a model that would assist in determining how genetic algorithms can be used in this field In addition, the developed model was also capable of solving problems in case the building projects consisted of one or several sub-projects. In sum, the aim of the study was to develop a model for leveling resources for cases consisting of single or multiple projects within the context of planning activities for building construction project management based on following assumptions: • The project is time constrained, but no limitations are involved with respect to the availability of resources. • One type of resources is used during the activities (money and workforce) • Leveling methods are used (the heuristic model and the genetic model). The Critical Path Method (CPM) was used for illustrating the operations performed in the provided examples, and to calculate the planning times. Two different computer programs were developed for the heuristic algorithm model (the traditional method) and the proposed genetic algorithm model, and the two models were compared in the given/evaluated cases. The results of these comparisons were illustrated using tables.